Recipient-Matching of Passenger Leukocytes Prolongs Survival of Donor Lung Allografts in Miniature Swine - Madariaga, Maria Lucia L. (Transplantation, 2015)
BACKGROUND: Allograft rejection continues to be a vexing problem in clinical lung transplantation, and the role played by passenger leukocytes in the rejection or acceptance of an organ is unclear. Here we tested whether recipient-matching of donor graft passenger leukocytes would impact graft survival in a preclinical model of orthotopic left lung transplantation. METHODS: In the experimental group (Group 1), donor lungs were obtained from chimeric swine, in which the passenger leukocytes (but not the parenchyma) were MHC-matched to the recipients (n=3). In the control group (Group 2), both the donor parenchyma and the passenger leukocytes were MHC-mismatched to the recipients (n = 3). RESULTS: Lungs harvested from swine previously rendered chimeric by hematopoietic stem cell transplantation using recipient-type cells showed a high degree of passenger leukocyte chimerism by immunohistochemistry and flow cytometry. The chimeric lungs containing passenger leukocytes matched to the lung recipient (Group 1) survived on average 107 days (range 80–156). Control lung allografts (Group 2) survived on average 45 days (range 29–64; p<0.05). CONCLUSION: Our data indicate that recipient-matching of passenger leukocytes significantly prolongs lung allograft survival.